Topical cyclosporine A 0.1% for treatment of corneal subepithelial infiltrates in a 15-year-old patient - Rogaczewska, Małgorzata; Stopa, Marcin (Klinika Oczna / Acta Ophthalmologica Polonica, 2020)
We present a case of a 15-year-old female patient with multiple corneal opacities of the left eye secondary to epidemic keratoconjunctivitis a year earlier. Due to the elevated intraocular pressure on topical steroid therapy, cyclosporine A eye drops were started. The visual acuity improved from 0.2 to 1.0 and remained stable during 3-year follow-up. No side effects were noted. The regression of corneal subepithelial infiltrates was monitored by anterior segment optical coherence tomography imaging.